Soviet Military Assistance to Egypt During Early Presidency of Anwar Sadat (September 1970 — October 1973) - V. A. Kuzmin; M. M. E. Abdalla (Научный диалог)
This article analyzes the military-technical cooperation between the USSR and Egypt in the early 1970s. Central to this study is the political interaction between the two nations, as well as the challenges faced by Cairo and Moscow following Anwar Sadat’s rise to power. Particular attention is given to the factors that hindered the maintenance of a high level of Soviet military aid to Egypt during the period from 1971 to 1973. The research focuses on the political intentions of the leadership in both countries, with special emphasis on the bilateral relationship crisis in 1972. The study examines the impact of this crisis on the rearmament process of the Egyptian army and analyzes the strategies employed to secure necessary armaments for Egypt, culminating in President Sadat’s decision to initiate war with Israel in October 1973. The novelty of this research lies in its analysis of materials from Russian archives and memoirs of Egyptian political and military figures in Arabic. The relevance of this study is underscored by its demonstration of the complexities of the political processes occurring in Egypt that influenced the nature and level of SovietEgyptian relations, particularly in the realm of military-technical cooperation during 1970–1973.